Altered relationship between R-R interval and R-R interval variability in endurance athletes with overtraining syndrome - Kiviniemi, A. M.; Tulppo, M. P.; Hautala, A. J.; Vanninen, E.; Uusitalo, A. L. T. (Scandinavian Journal of Medicine & Science in Sports, 2014)
Autonomic dysfunction decreases within-subject correlation between R-R interval length (RRi) and vagally mediated RRi variability in cardiac disease. We tested the hypothesis that overtraining syndrome (OTS) may also weaken this relationship. Nine OTS and 10 control endurance athletes underwent 24-h electrocardiogram monitoring, which was repeated in eight OTS and nine control athletes after 6 months, when two OTS athletes still had symptoms of OTS. The power of high-frequency (HF) oscillations of RRi was analyzed in 5-min epochs over the whole recording. Quadratic regression was performed between 5-min values of RRi and log-transformed (ln) HF to obtain R2 for each recording. The relationship between RRi and HFln was higher in the OTS athletes than controls [R2: 0.87 (90% confidence interval, CI: 0.84-0.89) vs 0.78 (90% CI: 0.72-0.84); P = 0.034; effect size = 1.22]. Large decrease in R2 was observed in six recovered OTS athletes after 6 months follow-up [deltaR2: -0.12 (90% CI: -0.25-0.01); P = 0.11; effect size = 1.44] with no changes in the controls. Mean values of RRi and its variability did not differ between the groups. The within-subject correlation between RRi and vagally mediated RRi variability was stronger in endurance athletes with OTS compared with controls. The present findings may improve the detection of OTS and recovery from OTS in endurance athletes.